2017
DOI: 10.1590/0004-282x20170123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an alternating work shift on air traffic controllers and the relationship with excessive daytime sleepiness and stress

Abstract: Objective: To evaluate symptoms of stress and excessive daytime sleepiness (EDS) in air traffic control (ATC) officers in Brazil. Methods: Fifty-two ATC officers participated, based at three air traffic control units, identified as A, B and C. Stress symptoms were assessed using the Lipp Inventory of Stress Symptoms for Adults, and EDS by the Epworth Sleepiness Scale. Results: The sample mean age was 37 years, 76.9% of whom were male. Excessive daytime sleepiness was identified in 25% of the ATC officers, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
5
0
4
Order By: Relevance
“…Sleepiness constituted an important part of absenteeism and delay to work in our study. Sleepiness implies a propensity to doze off or fall asleep unintentionally during the day, especially in passive situations (Freitas et al, 2017). The sleepiness rate was 5.2% in our study and was an independent risk factor for the subjects who reported delay to work.…”
Section: Discussionmentioning
confidence: 99%
“…Sleepiness constituted an important part of absenteeism and delay to work in our study. Sleepiness implies a propensity to doze off or fall asleep unintentionally during the day, especially in passive situations (Freitas et al, 2017). The sleepiness rate was 5.2% in our study and was an independent risk factor for the subjects who reported delay to work.…”
Section: Discussionmentioning
confidence: 99%
“…Jou et al (2013) found that the highest trigger of ATCO stress was the air traffic load, including the stricter attentions required during traffic conflict resolution. However, prior studies have only concentrated on shift (Freitas et al, 2017), eye movement (Renata et al, 2018) and traffic load (Prevot et al, 2012; Westin et al, 2013; Yang and Dattel, 2017) as the main causes of stress, fatigue and workload.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, an association was observed between the presence of sleep disorders and clinical outcomes such as depression, burnout, diabetes and cardiovascular disease. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)26) In the other study, the clinical and polysomnography data of 761 military officers were evaluated retrospectively, showing a high prevalence of OSAS (27.2%), insomnia (24.7%) and insufficient sleep time (41.8%). (14,27) The main predictors of OSAS were obesity, male gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 84.6% belonged to the same air traffic control unit, which is characterized by a greater movement of aircraft with 24-hour operation and the service schedule in alternate shifts. (23) A study of 464 police officers working in Buffalo, New York, USA between 2004 and 2009 provided information on the effect of long and short-shift work on the number of circulating white blood cells. Shift work can lead to rupture of blood components by the circadian influence of the immune system, which in the end can result in various chronic diseases.…”
Section: Discussionmentioning
confidence: 99%